A vida nua como Arché da biopolitica em Giorgio Agamben - Batista, Tarciano Silva (2019)
The current work has the main goal to examine human life as a political issue, that is, to analyze the bare, or naked, life as the origin of biopolitics from the conceptual exposition carried out by Agamben in his Homo Sacer 1: sovereign power and bare life (1995). Thus, this discussion aims to comprehend how the author reflects on the relation between politics and life in contemporaneity, in the sense that as a political aspect or as the link between life and politics, nature and culture, zoê and bios, we can elucidate how bare life (or mere life, in terms of Walter Benjamin) constitutes the arche (origin) of western politics. That said, it is important to remark that this bare life presents itself under the limits of violence of the government, included by the “papers of barbarity” in a political frame of devices and techniques of exclusion. In this perspective, our philosophical issue is presented as follows: what is the relation between life and politics when, divided in the origin and articulated by the government, human life (citizen, conscious and free) becomes naked, that is, killable by the unpunishable sovereign decision, and biopolitics, which is the management of life of individuals, becomes a state of exception? In order to carry out that discussion, Agamben thinks the “camp” (of refugees, of extermination, or death, as well as, we could say, the senzalas, or slave quarters, and the colonial farms of the masters) as a constituent of the contemporary paradox of sovereignty, because at the same time it creates naked life, it produces its total exclusion, becoming the paradigm of western politics. Therefore, our hypothesis is that naked life is the principle (arche) of biopolitics in Agamben’s thought and that the forms-of-life must compose the unitary center of reflection of contemporary political thinking.